Team situation awareness and the anticipation of patient progress during ICU rounds. Issue 12 (23rd June 2011) - Reader, Tom W; Flin, Rhona; Mearns, Kathryn; Cuthbertson, Brian H
Abstract : Background: The ability of medical teams to develop and maintain team situation awareness (team SA) is crucial for patient safety. Limited research has investigated team SA within clinical environments. This study reports the development of a method for investigating team SA during the intensive care unit (ICU) round and describes the results. Methods: In one ICU, a sample of doctors and nurses (n=44, who combined to form 37 different teams) were observed during 34 morning ward rounds. Following the clinical review of each patient (n=105), team members individually recorded their anticipations for expected patient developments over 48 h. Patient-outcome data were collected to determine the accuracy of anticipations. Anticipations were compared among ICU team members, and the degree of consensus was used as a proxy measure of team SA. Self-report and observational data measured team-member involvement and communication during patient reviews. Results: For over half of 105 patients, ICU team members formed conflicting anticipations as to whether patients would deteriorate within 48 h. Senior doctors were most accurate in their predictions. Exploratory analysis found that team processes did not predict team SA. However, the involvement of junior and senior trainee doctors in the patient decision-making process predicted the extent to which those team members formed team SA with senior doctors. Conclusions: A new method for measuring team SA during the ICU round was successfully employed. A number of areas for future research were identified, including refinement of the situation awareness and teamwork measures.